Serological and molecular prevalence of Brucella spp. among livestock species in Rajasthan, India - Meena, Dharm Singh; Sharma, Lata; Bishnoi, Jyoti; Soni, Monika; Jeph, Nirmal Kumar; Galav, Vikas; Sharma, Sandeep Kumar (Frontiers in Veterinary Science, 2023)
A seroprevalence and molecular study was carried out in six districts of the state of Rajasthan, India to detect brucellosis in major livestock species. This study involves the testing of 3,245 livestock samples using the Rose Bengal Plate Test (RBPT), Indirect Enzyme-Linked Immunosorbent Assay (i-ELISA), and genus-specific polymerase chain reaction (PCR) markers for molecular diagnosis of the disease. In the tested samples, seroprevalence was 5.06% (CI: 1.96–8.15) using the RBPT test and 6.88% (CI: 1.98–11.78) using the i-ELISA test, while the cumulative seroprevalence (RBPT and i-ELISA) was 3.63% (CI: 0.44–6.83). The prevalence of the disease was 1.27% (CI: 0.56–3.11) when tested using molecular markers. The highest prevalence of brucellosis was detected in Cattle (7.00, 3.22%), followed by camels (5.50, 2.50%), buffalo (2.66, 0.00%), sheep (2.43, 0.41%), and goats (0.58, 0.23%) when serological (cumulative) and molecular diagnosis were considered preferred methods of detection. Cattle (3.22%) and camels (2.50%) also showed a high prevalence of disease when tested using molecular markers. The results of this study reveal that cattle, camel, and sheep brucellosis is prevalent in the study areas.